2020
DOI: 10.1186/s12967-020-02249-4
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of p66Shc prevents hyperandrogenism-induced ovarian oxidative stress and fibrosis

Abstract: Background: Rats with hyperandrogen-induced polycystic ovary syndrome (PCOS) have been shown to develop ovarian oxidative stress (OS) and fibrosis. The Sirt1 agonist, resveratrol, can reduce OS through inhibiting p66Shc in other models of OS. Methods: We created a rat PCOS model with increased OS levels following treatment with one of the two androgens, dehydroepiandrosterone (DHEA) and dihydrotestosterone (DHT). The PCOS related features were determined by measurement of malondialdehyde (MDA) and superoxide d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…Female rats (23 days old) were intraperitoneally injected with pregnant mare serum gonadotropin (20 IU), and 48 h after injection, rats were killed by cervical dislocation. Isolation and primary culture methods of GCs were previously described [ 5 , 6 ]. The primary GC suspensions were cultured in DMEM-F12 medium supplemented with 10% fetal bovine serum (Gibco, Grand Island, USA) and 1% penicillin–streptomycin (Gibco) at 37°C (95% relative humidity, 5% CO 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Female rats (23 days old) were intraperitoneally injected with pregnant mare serum gonadotropin (20 IU), and 48 h after injection, rats were killed by cervical dislocation. Isolation and primary culture methods of GCs were previously described [ 5 , 6 ]. The primary GC suspensions were cultured in DMEM-F12 medium supplemented with 10% fetal bovine serum (Gibco, Grand Island, USA) and 1% penicillin–streptomycin (Gibco) at 37°C (95% relative humidity, 5% CO 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Most studies report that hyperandrogenism is the main cause of infertility owing to PCOS. Our previous research showed that hyperandrogen dramatically augments oxidative stress (OS) and fibrotic factor activation in the ovary [ 5 ] and stimulates chronic low-grade inflammation in the ovary to activate the NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome, further inducing ovarian granulosa cell (GC) pyroptotic death, follicular dysfunction, and ovarian interstitial cell fibrosis [ 6 ]. GCs may undergo excessive OS, chronic low-grade inflammation, and increased apoptosis [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many antioxidant compounds have been proposed to regulate nfe2l2 expression by modulating DNA methylation at the CpG sites of the promoter sequence of nfe2l2. Resveratrol, widely found in grapes, mulberries, peanuts, and red wine, is a natural phenolic compound with strong anti-inflammatory, antioxidant, and anti-cancer properties (65)(66)(67)(68). Resveratrol was shown to prevent HG-induced oxidative stress in HepG2 cells via suppressing methylation of Nfe2l2, which attenuated HGinduced triglyceride accumulation (36).…”
Section: Epigenetic Modifications Of Nrf2 By Pharmacological Agentsmentioning
confidence: 99%
“…Park et al (2020) demonstrated that SIRT1 can downregulate ROS and form a complex with FOXO3a in cells, which can improve the ability of FOXO3a to induce cell cycle arrest and promote cell survival. Recent findings have indicated that resveratrol, a plant polyphenolic compound, can enhance SIRT1 and decrease ovarian oxidative stress as well as inhibit phosphorylation of p66Shc, both in vivo and in vitro (Wang et al, 2020). Thus, in terms of follicular development, there undoubtedly exists an interactive relationship between ROS, SIRT1, and FOXO3a.…”
Section: Oxidative Stressmentioning
confidence: 99%